Evaluación de las variables físicas en el agua del humedal La Segua Chone en periodo seco y lluvioso del 2019 - Cevallos Mendoza, Marcos Froilán (2019)
The purpose of the research was to evaluate the physical variability of the La Segua wetland of the Chone canton in two seasons: dry and rainy, in the months of March and May, transition time between seasons, for which a descriptive exploratory study was carried out in the wetland, in which the perimeters for the sampling and sample collection sites were established, obtaining a perimeter of 100 m round in the dry season and 300 m for the rainy season, both selected from the existing agricultural use channel in the wetland For the recording of the changes in the body of water, three thematic information maps (study area, water map, sampling points) were made, the sampling sites were georeferenced and the anthropic activities carried out in the area of direct influence were recorded. of sampling, which was carried out under the technical standard INEN 2176-2013. For physical quality, temperature, salinity, pH, electrical conductivity, turbidity and total dissolved solids were evaluated, the measurement was in situ at different depths (1 m; 0,50 m and 0,25 m) and at different daily time scales (06h30 am; 07h30 am; 08h30 am; 18h30 pm; 19h30 pm and 20:30 pm) The variation evaluation was carried out through a 95% confidence analysis using the software InfoStat The results show a significant difference for the turbidity and color parameters in the rainy season, in addition to presenting a difference, the results with greater variability are outside the limits established in the TULSMA, turbidity with a value of 470,96 NTU well above the regulations that are less than 50 NTU.